The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0022034512463239
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Pain, and Pressure—Purinergic Signaling in Oral Tissues

Abstract: Signaling by extracellular purines such as ATP and adenosine has implications for dental research on multiple levels, with the association of purinergic signaling with inflammation, mechanical strain, and pain making the system particularly relevant for the specific challenges in the oral cavity. Oral tissues express a variety of G-protein-coupled P2Y receptors for ATP and P1 receptors for adenosine in addition to ionotropic P2X receptors for ATP. When these receptors are combined with the plethora of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…P2X7 is an ion-gated channel that can participate in apoptotic cell death, and its ligand, extracellular adenosine triphosphate (eATP), is a prototypic DAMP, being implicated in IL-1β cleavage and secretion from proinflammatory cells (Pelegrin et al 2008). A large body of evidence indicates that stimulation by eATP, adenosine, and related compounds can affect many additional facets of oral pathophysiology, as recently reviewed (Lim and Mitchell 2012). Yilmaz et al (2008) showed that P. gingivalis stimulates synthesis of pro-IL-1β, but this first signal is not able to activate the NLRP3 inflammasome in gingival epithelial cells; however, addition of an exogenous source of ATP promoted secretion of the mature IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…P2X7 is an ion-gated channel that can participate in apoptotic cell death, and its ligand, extracellular adenosine triphosphate (eATP), is a prototypic DAMP, being implicated in IL-1β cleavage and secretion from proinflammatory cells (Pelegrin et al 2008). A large body of evidence indicates that stimulation by eATP, adenosine, and related compounds can affect many additional facets of oral pathophysiology, as recently reviewed (Lim and Mitchell 2012). Yilmaz et al (2008) showed that P. gingivalis stimulates synthesis of pro-IL-1β, but this first signal is not able to activate the NLRP3 inflammasome in gingival epithelial cells; however, addition of an exogenous source of ATP promoted secretion of the mature IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…It causes progressive irreversible damage that leads to tooth loss 1. There is a link between periodontitis and systemic diseases such as diabetes and cardiovascular disease, which seriously impact patients' quality of life 2.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors, such as tumour necrosis factor alpha (TNF-a) [9], nitric oxide (NO) [10], interleukin (IL)-33 [11], and several adhesion molecules [8], also participated in the pathogenesis of synovitis. Interestingly, these inflammatory cells and cytokines were reported to be involved in pain severity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%